When bad news is sugarcoated: Information distortion, organizational search and the behavioral theory of the firm - Fang, Christina; Kim, Ji‐Hyun (Jason); Milliken, Frances J. (Strategic Management Journal, 2014)
Most work in strategy and organization theory assumes that performance feedback is straightforward to interpret and truthfully reported. We raise the following question: How might the systematic distortion of negative performance information affect organizational learning and future performance? We formulate a model where (1) members do not always report the truth about what they know about their performance level, especially when performance is below aspiration and (2) their propensity to distort information is subject to social influence. We find that organizations that are characterized by a high level of information distortion tend to perform more poorly but that the effect of a low rate of sugarcoating may, in some conditions, be more benign than the literatures seem to suggest. Copyright © 2013 John Wiley & Sons, Ltd.